Meningkatkan Kualitas Blended Learning: Case Study Menggunakan CoI Model - Lydiawati Kosasih Asalla (Bina Nusantara University, 2010)
This article discusses several considerations in the education industry to achieve good quality learning by using advances in technology such as blended learning, and it uses the Community of Inquiry model as a comparison to raise quality of the blending learning program. Other aspects include on how to raise quality of a discussion as an improvement of knowledge management.